Evaluasi Kesesuaian Obat Dan Dosis Antihipertensi Pada Pasien Hipertensi Rawat Jalan Di Rumah Sakit Royal Prima - Sosa Ester Kristiani Lase; Muhammad Yunus; Astriani Natalia Br Ginting (Jurnal Sains Farmasi Dan Kesehatan, 2025)
This study was conducted to assess the appropriateness of antihypertensive medication selection and dosage and to analyze the cost-efficiency of therapy in outpatients with hypertension at Royal Prima Hospital, Medan. This study used a retrospective descriptive method, with data collected from the medical records of 42 patients. Evaluation of therapy effectiveness and costs was conducted using a Cost-Effectiveness Analysis (AEB) approach, calculating the Average Cost-Effectiveness Ratio (ACER) and the Incremental Cost-Effectiveness Ratio (ICER). Symptoms associated with hypertension can be avoided by reducing excess weight (obesity), controlling salt intake, engaging in regular physical activity, quitting smoking, and taking medication regularly. A hypertension prevalence survey found that the prevalence of hypertension in Indonesia among the population aged 18 years and over is 31.3% for men and 31.9% for women, out of the total population aged 18 years and older. In 2008, the number of hypertension sufferers reached 32%, with the majority of patients aged > 25 years. The results showed that all patients (100%) received appropriate antihypertensive therapy based on standard clinical guidelines, both in terms of drug selection and dosage. The most commonly used drug combination was ARB and CCB, found in 23.81% of patients. The combination of a non-DHP CCB + ARB + ​​loop diuretic + alpha-blocker demonstrated the highest therapeutic effectiveness (100%) with the lowest average cost of IDR 680,000, thus being considered the most cost-effective regimen according to the ICER analysis. Meanwhile, several other therapy combinations that required higher costs but provided less effectiveness were categorized as cost-inefficient. These findings emphasize the importance of rational evaluation of antihypertensive therapy, particularly in terms of treatment appropriateness and cost-efficiency, to support optimal clinical outcomes and appropriate resource utilization.